Front Cover: Cover Image, Volume 25, Issue 1. Issue 1 (2nd December 2021) - Boulinguez‐Ambroise, Grégoire; Pouydebat, Emmanuelle; Disarbois, Éloïse; Meguerditchian, Adrien
Abstract : The cover image is based on the Paper Maternal cradling bias in baboons: The first environmental factor affecting early infant handedness development? by Grégoire Boulinguez‐Ambroise et al., https://doi.org/10.1111/desc.13179 .